COMPARATIVE DESCRIPTION OF THE MORPHOLOGICAL INDICATORS OF THE GESTINAL GLAND IN LIVER INJURY UNDER EXPERIMENTAL CONDITIONS - Ruziyeva Dilbar Uktamovna (TADQIQOTLAR, 2025)
Annotation: Infertility is a disease that affects millions of men of reproductive age worldwide today, and its negative impact on families and society makes this pathology an urgent global medical and social problem. Male infertility can be caused directly or indirectly by many diseases and factors. Liver damage negatively affects the morphofunctional parameters of the testicles.